The complete guide to organic livestock farming : everything you need to know about natural farming on a small scale - Paajanen, Terri (Ocala, Fla. : Atlantic Pub. Group, 2011)
Small scale farming has grown greatly in popularity during the last two decades, with a greater turn in public awareness toward locally grown, organic, grass fed products that have not been modified, chemically altered, or poorly fed. For that reason, those looking to start a small scale farm and raise livestock have a greater chance than ever before to take advantage of the new market for small scale goods. This book will show any potential small scale farmer how to start raising their livestock and marketing it to the organic, natural lifestyle community that so fervently seeks out these products. You will learn how to start the basic outline for your new small farm, including which livestock to raise, how to build their pens and habitat, and what you will be feeding them to maintain a healthy, organic farm. You will learn the basics of animal husbandry, from genetics and breeding to feeding, building locations, and proper health and reproduction care. You will learn how to find yourself in the right niche for selling your products and what legalities you must see to as well as the butchering and processing phase Hundreds of hours of in-depth interviews have been conducted for this book with top experts in farm management to provide you with details about farm planning, financial planning, and proper livestock planning. A complete appendix will detail the various breeds and needs of cattle, chickens, goats, horses, pigs, and sheep to help you select the right livestock for your farm. In addition, you will learn the basic composition of most feeds, different grasses and legumes you can use, and find a plethora of outside resources to utilize. For anyone with dreams of a small farm and raising livestock in their future, this is a book for you
Keywords: Livestock; Animal culture; Farms, Small